Exploring teacher agency and instructional practices in implementing the Merdeka Curriculum: A qualitative study of English Language teaching in Indonesian Senior High Schools - Tri Achmad Efendi; Alvin Apriliano Arijanto (Priviet Social Sciences Journal, 2025)
This study explored English teachers' practices in the implementation of English Language Teaching (ELT) under the Merdeka Curriculum in Indonesian senior high schools.  Employing a qualitative case study approach, the researchers collected data through semi-structured interviews with three English teachers from three schools. This study investigated how teachers adapt the curriculum to classroom practice and their perceptions of students’ engagement and learning outcomes. To provide contextual insight, placement tests (vocabulary and reading tests) and writing test results were examined to illustrate the alignment between teaching approaches and outcomes. The findings revealed that teachers who adopted student-centered and collaborative strategies reported higher student motivation and stronger motivation on both tests. In contrast, a textbook-oriented or teacher-centered approach is associated with limited student progress. Therefore, this study emphasizes the critical role of teacher agency and the availability of resources in realizing the goals of the Merdeka Curriculum.